Shear Thickening Fluids Comparative Analysis Composed of Silica Nanoparticles in Polyethylene Glycol and Starch in Water. (8th December 2020) - Mankarious, Remon A.; Radwan, Mostafa A.
Abstract : Shear thickening fluid (STF) occurs in dispersions of highly condensed colloid particles and is categorized as a non-Newtonian fluid whose viscosity increases under shear loading which makes them beneficial in protective and impact resistance applications. The aim of this study is to synthesis two different STFs and characterize their microstructural properties to provide a data base for comparing the final macrobehavior of the two fluids under mechanical testing. Therefore, fumed silica and polyethylene glycol STF and starch with water STF-based dispersions were prepared. The particle size, zeta potential, SEM micrographs, and rheological analysis were performed for each type of STF. The effect of filler concentration was observed by using 10–30 weight% filling material. The rheological properties of STFs show higher viscosity measurements at same shear rates for starch/water STF than silica/PEG with maximum viscosity reaching 523.6 Pa s and 178.9 Pa s, respectively. Larger starch particle size over silica recorded as 303.7 nm and 16.49 nm, respectively, and zeta potential analysis recorded particle electrostatic charges as 22.6 mV and 12.8 mV, respectively, leading to more dispersion stability and obvious thickening effect at higher particle concentration leading to greater jump in viscosity at sudden shear rate. The results indicate the capability of trying more protective applications with more flexibility and less thickness when STF is implemented and a good database for the fluids to choose from according to their behavior.